Il platonismo di Ariosto (ENTHYMEMA, 2013)
Starting from the moon episode in Orlando Furioso,  the essay put in aesthetic and cultural perspective the peculiar way in which Ariosto translates in written form the platonic contrast between Idea and copy. Ariosto is thus integrated into the platonic tradition of the Renaissance, taking into account his links with the cultural environment of Ferrara at the time.